Housemates - Watts, Alison (Oxford University Press, 2010)
Content: Chris leaves his home in a small town in Australia to go and study at the University of Sydney. He needs to find somewhere to live. But it's not easy to find a house to share in a big city. Every house has its problems, and not all of Chris's housemates are easy to live with. In fact, some of them are very difficult people! Can Chris find the house that he needs with housemates that he can live with?